Novel T-cell subsets as non-invasive biomarkers of vascular damage along the predialysis stages of chronic kidney disease - Martín-Vírgala, Julia; Miranda-Prieto, Daniel; Fernández-Villabrille, Sara; Martín-Carro, Beatriz; González-García, Nerea; Bande-Fernández, Joaquín; Díaz-Corte, Carmen; Fernández-Martín, José Luis; Alonso-Montes, Cristina; Suárez, Ana; Panizo, Sara; Naves-Díaz, Manuel; et al. (Frontiers in Medicine, 2024)
Introduction. Cardiovascular disease is the major cause of premature death in chronic kidney disease (CKD) and vascular damage is often detected belatedly, usually evaluated by expensive and invasive techniques. CKD involves specific risk factors that lead to vascular calcification and atherosclerosis, where inflammation plays a critical role. However, there are few inflammation-related markers to predict vascular damage in CKD. This study aimed to investigate immune populations in pre-dialysis patients to (i) identify subset alterations, (ii) assess longitudinal changes, and (iii) evaluate their applicability as biomarkers of subclinical vascular indices. Methods. 43 pre-dialysis CKD patients in stages CKD-2 to CKD-5 and 38 controls were recruited at baseline and after 18-month follow-up. Aortic stiffness was determined by carotid-femoral pulse wave velocity (PWV) and abdominal aortic calcification was quantified by the Kauppila index on X-rays. Carotid intima-media thickness, the number of carotid plaques and adventitial neovascularization were evaluated by Superb Microvascular Imaging. Peripheral blood mononuclear cells were isolated and immune cell populations were assessed by flow cytometry: senescent T cells (CD4+CD28null), Tang (CD3+CD31+CD184+) and derived subsets, and monocyte subsets (classical, intermediate and non-classical; and ACE expression). Results. senescent T cells were increased in CKD. Despite Tang levels were unchanged compared to controls, this subset exhibited enhanced immunosenescence traits (CD28null and inverted CD4+/CD8+ ratio) in CKD. Furthermore, Tang were negatively correlated with CKD progression. Slight alterations within monocyte subsets were observed. These findings were validated at the 18-month follow-up. Tang were correlated with several subclinical indices, and further analyses revealed an independent effect on PWV and their potential value as biomarkers. Intermediate monocytes were positively correlated with PWV. Conclusions. Pre-dialysis CKD stages are hallmarked by alterations in immune cell populations related to vascular homeostasis, including early T-cell immunosenescence traits and a stage-dependent Tang depletion, which was independently related to vascular stiffness. All these features were replicated upon follow-up, thus providing validation towards our results. Our findings pave the ground for future studies addressing the functional contribution of these cellular mediators at the local level, assessing their potential predictive value in the long-term and implementing preventive strategies in the clinical setting.